"You can't just eat 16 teaspoons of sugar so why would you drink 16 teaspoons' worth of sugar?": a qualitative study of young adults' reactions to sugary drink warning labels - C Miller; K Wright; J Dono; S Pettigrew; M Wakefield; J Coveney; G Wittert; D Roder; S Durkin; J Martin; K Ettridge (BMC, 2022)
Abstract Background Several jurisdictions have introduced nutrient warning front of pack (FoP) labels in an effort to curb consumption of ultra-processed foods and beverages high in free sugars (sugars added to foods and beverages, and sugars naturally present in honey, syrups, fruit juices and fruit juice concentrates). This study aimed to explore consumer understanding and perceptions of FoP warning labels that convey different nutritional and health information messages regarding the consumption of sugary drinks. Methods Sixteen focus groups were held with 4-8 young adults per group (aged 18-24; n = 105 participants in total) stratified by education level, location (rural centres, large cities) and gender (males, females) to ensure diversity. Labels shown to participants during group discussions included text warning labels of health effects, exercise equivalents, calorie/kilojoule information and sugar content as a "high in" label and as teaspoons (text and pictograms). Thematic analysis was undertaken. Results Four themes were identified related to participants' perceived effectiveness of labels: the extent to which labels were perceived to be useful, relevant and credible; the extent to which a label elicited shock or disgust (perceived aversiveness); the extent to which the label message was resistant to self-exemption; and participants' perceived potential of the label to reduce purchasing and consumption behaviour. Across all four themes, labels communicating the number of teaspoons of sugar in a sugary drink (whether by text or pictogram) were perceived as the most impactful, resistant to self-exemption and to have the greatest potential to reduce consumption, with enhanced reactions to the pictogram label. Labels depicting health effects, exercise equivalents, calorie/kilojoule information or a general 'high in sugar' warning were perceived by consumers to be less effective in one or more themes. Conclusions Labels conveying the amount of sugar in a beverage in teaspoons were perceived as highly factual, relatable and interpretable, and as having the greatest potential to impact consumption attitudes and intentions. Further quantitative studies are required to compare the potential effectiveness of the teaspoons of sugar labels in reducing purchasing and consumption behaviour than other alternative warning labels, such as health effects or "high in" sugar labels.